Becoming Who You Are: Insights on the True Self From Thomas Merton and Other Saints - Twomey, Gerald S. (Cistercian studies quarterly, 2008)
The article reviews the book "Becoming Who You Are: Insights on the True Self From Thomas Merton and Other Saints," by James Martin.